Empirical study on agricultural drought adaptation of typical rainfed areas in Shidian County, China. (June 2018) - Wang, Zhiqiang; Ma, Qing; Wang, Jiaxin; Chen, Siyu; Fan, Yida; Deng, Lan
Abstract: As global mean surface temperature continues to rise, increasing evidences have shown that social and natural systems are deeply influenced by climate change. The government and farmers' awareness, as well as measures to adapt to these climate-driven changes, are critical for local sustainable development. Rainfed areas are the most sensitive to environment change. In this study, we established a conceptual model of the relationship among environment changes, development demand and human adaptation to analyse the mechanism of agricultural drought adaptation of typical rainfed areas based on an empirical research at the government and farmers level. The findings show that under scenarios of climate change, the study area of drought risk has continued to expand. Under this circumstance, the government and farmers have constantly taken measures to adjust the development demand to adapt to agricultural drought. Interactions among environmental changes, development demand and adaptation measures have kept the regional nature-society-economy compound ecosystem in dynamic balance. In addition, the effects of these adaptation measures always have an inertia that may lead to a profound influence on the region, which should be considered during the process of adaptation strategy planning. This study reveals the mechanism of adaptation from a macroscopic perspective and may provide some references for implementing drought adaptation strategies in other rainfed areas.